2014
DOI: 10.1094/pdis-01-14-0002-pdn
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Iris yellow spot virus Infecting Allium tuberosum in India

Abstract: Allium tuberosum L., commonly known as garlic chives, is an important spice in northeastern India as well as in many other parts of the world. Iris yellow spot virus (IYSV; genus Tospovirus, family Bunyaviridae) is an important pathogen of onion (4) and other related Alliums such as garlic (3) and leek (2). During April 2013, symptoms potentially induced by IYSV such as chlorotic and straw-colored spindle-like lesions were observed on leaves of A. tuberosum accession Hanzong Winter (CGN 20779) plants in the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…The presence of INSV and IYSV in alliums is probably due to their adaptation to new crops, the importation of infected bulbs, and the transmission from infected nearby crops and volunteer plants that contribute to disease spread by acting as reservoirs for the virus and the vector (Cooper & Jones, 2006). In addition to the cultivated alliums (e.g., garlic, leek, and onions), previous studies reported only small surveys of virus incidence in some wild and ornamental species (Bampi et al, 2015; Cramer et al, 2011; van Dijk, 1993; Dovas et al, 2001; Gawande et al, 2014; Paduch‐Cichal & Bereda, 2017; Scrace et al, 2015; Ward et al, 2009). Among the species identified as hosts of carla‐, poty‐, allexi‐ or orthotospoviruses, several have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of INSV and IYSV in alliums is probably due to their adaptation to new crops, the importation of infected bulbs, and the transmission from infected nearby crops and volunteer plants that contribute to disease spread by acting as reservoirs for the virus and the vector (Cooper & Jones, 2006). In addition to the cultivated alliums (e.g., garlic, leek, and onions), previous studies reported only small surveys of virus incidence in some wild and ornamental species (Bampi et al, 2015; Cramer et al, 2011; van Dijk, 1993; Dovas et al, 2001; Gawande et al, 2014; Paduch‐Cichal & Bereda, 2017; Scrace et al, 2015; Ward et al, 2009). Among the species identified as hosts of carla‐, poty‐, allexi‐ or orthotospoviruses, several have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…Some earlier studies investigated viruses in wild plants based on the idea that natural vegetation may serve as a reservoir for the disease (Cooper & Jones, 2006). To date, the occurrence of viruses, especially in cultivated crops such as garlic, onion, leek, and shallot has been well investigated worldwide (Chen et al, 2001; Chodorska et al, 2014; Conci et al, 2003; Cramer et al, 2011; Dovas et al, 2001; Godena et al, 2020; Klukáčková et al, 2007; Mahmoud et al, 2008; Ward et al, 2009) but viral infection of wild and ornamental Allium species in both natural and agricultural ecosystems is only occasionally tested (Bampi et al, 2015; Cramer et al, 2011; van Dijk, 1993; Dovas et al, 2001; Gawande et al, 2014; Paduch‐Cichal & Bereda, 2017; Scrace et al, 2015; Ward et al, 2009). Although viruses tend not to damage wild plants (Cooper & Jones, 2006), the abundance of Allium viruses in nature and their ability to move between hosts should be further explored for disease resistance (Khandagale et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…IYSV was firstly recorded in onion crops in Idaho, USA in 1989 [ 4 ] and then in the Netherlands in 1992, where it was characterized to be a new, distinct orthotospovirus from Iris hollandica [ 5 ]. Subsequently, IYSV was found to occur in [ 6 ] Brazil [ 7 ], Australia [ 8 ], Japan [ 9 ], Chile [ 10 ], Spain [ 11 ], Guatemala [ 12 ], Peru [ 13 ], India [ 14 ], and Egypt [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…IYSV was first reported in the USA in 1989 [12], after which the virus was reported in many other countries [11]. In India, it was first reported in onions in 2006, in garlic in 2010, and in chives in 2014 [9,10,23].…”
Section: Introductionmentioning
confidence: 99%